2015
DOI: 10.1111/eth.12420
|View full text |Cite
|
Sign up to set email alerts
|

European Roe Deer Increase Vigilance When Faced with Immediate Predation Risk by Eurasian Lynx

Abstract: These authors contributed equally to the study. AbstractPrey animals must balance antipredatory behaviour with foraging behaviour. According to the risk allocation hypothesis, prey increase antipredatory behaviour and reduce foraging activity during pulses of high risk, but with continuous risk, other activities must continue and antipredatory behaviour decreases despite the risk. We studied the impact of lynx presence on the vigilance behaviour of wild roe deer under conditions of (i) a pulsed elevated risk b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 72 publications
1
29
1
4
Order By: Relevance
“…Detection of a threat triggers flight responses modulated by sighting distance and habitat (Bonnot et al 2017). Roe deer are more vigilant in response to episodic risk (Benhaiem et al 2008, Eccard et al 2017. When hunted, roe deer may use refugia (Grignolio et al 2011) and alter habitat selection between daytime and nighttime (Bonnot et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Detection of a threat triggers flight responses modulated by sighting distance and habitat (Bonnot et al 2017). Roe deer are more vigilant in response to episodic risk (Benhaiem et al 2008, Eccard et al 2017. When hunted, roe deer may use refugia (Grignolio et al 2011) and alter habitat selection between daytime and nighttime (Bonnot et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly elk in the Yellowstone NP did not show wolves avoidance in winter (Mao et al ) and were suggested to rely on alternative anti‐predator strategies such as higher vigilance. Roe deer in the BFNP also showed small scales behavioural responses by increasing vigilance when confronted with pulses of high predation risk (Eccard et al ). At large spatial and temporal scales roe deer select habitats providing high quality forage over those decreasing predation risk (Samelius et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Migration has been found to be one strategy of ungulates to access high quality or abundant forage at all seasons (Hebblewhite and Merrill , Zweifel‐Schielly et al , van Beest et al , Cagnacci et al ). At a finer temporal scale, behavioural decisions are governed by short‐term responses to immediate stimuli, such as the circadian rhythm (Ensing et al ), rumination cycles in some herbivore species (Kamler et al ), weather (Ewald et al ), olfactory cues (Eccard et al ), or disturbance (Ciuti et al ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Living in groups has additional demonstrable benefits, such as improved predator detection (Kie, ; Lima, ; Pulliam, ), reduced probability of being predated once detected (dilution and confusion effects; Lehtonen & Jaatinen, ), and less individual time allocated to vigilance (collective vigilance; Lima & Dill, ; Childress & Lung, ; Creel et al., ). Habitat structure can shape predator–prey interactions through changes in visibility and the presence of either cover refuges or escape impediments (Eccard, Meißner, & Heurich, ; Jarman, ; Ripple & Beschta, ). In this sense, habitat openness will set the maximum group size, while predation risk will limit the minimum size (Jarman, ).…”
Section: Introductionmentioning
confidence: 99%